Application of 2D Electrical Resistivity Method for Site Investigation in the State Company for Glass and Refractories in Ar-Ramadi City, Iraq - Salman, Amina M.; Al-Rahim, Ali M. (Iraqi Journal of Science, 2023)
2D Electrical Resistivity has been applied at three selecting areas within the study area using Dipole-dipole and Wenner arrays with an a-spacing of 1 m, and the profile length was 120 m for both. The total data points were 4455 reads for Dipole-dipole, and the total data points for Wenner were 2340 reads, and the depth of each array was 15.4 m and 20.2 m, respectively. The 2D inverse results indicate the resistivity anomalies approximately at depth (2 - 7.8) m formed as a weakness zone lies within the quaternary and Injana Formation deposits and interbedded with secondary gypsum and gypcretes. Additionally, the inverse resistivity distribution model demonstrated that the area is impacted by groundwater that is interaction with sand, silt, and clay of the subsurface layers due to the gypsiferous and gypcrete deposits. They are distinguished by their ability to interact with water, whether it is surface or underground, and as a result, cause the emergence of a set of cavities and voids that may be filled with sediments that contain high levels of water and cause soil to wet. As well, the investigation gives the ideal array as Dipole-dipole rather than Wenner array due to its better in signal to noise ratio and provides the most suitable resolution for these applications, as well as the study, recommends conducting engineering and site investigations of the soil and determining the type of soil and the appropriate treatment methods that can overcome these problems.